EVALUASI BORDER CONTROL MANAGEMENT PLBN SKOUW DALAM MENEGAKKAN FUNGSI PENGAWASAN DAN KEAMANAN KEIMIGRASIAN - Ledyana Hanna Basna; Virra Wirdhiningsih; Wisnu Widayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Border Crossings of Indonesia (PLBN) Skouw is one of the main gateways of Indonesia that shares a direct border with Papua New Guinea. To uphold the functions of supervision and maintain national security, the Directorate General of Immigration implements the Border Control Management (BCM) system as the primary instrument in immigration checks. This study aims to evaluate the effectiveness of BCM usage at PLBN Skouw in the context of immigration functions, namely the supervision of foreigners and guarding against cross-border threats. The method used is qualitative descriptive with a documentary study approach and regulatory analysis, supported by secondary data from relevant agency reports. The research results show that the BCM system has supported the efficiency of the inspection and monitoring process of border crossers through the integration of biometric data and facial recognition systems. However, challenges were found in network infrastructure, human resource readiness, as well as the use of unofficial routes by local communities. Therefore, it is necessary to enhance technical capacity, socialize with border communities, and strengthen inter-agency synergy in order to optimize the function of BCM as the main instrument for monitoring and protecting national sovereignty.